Radial structure and property relationship in the thermal stabilization of PAN precursor fibres. (May 2017) - Nunna, Srinivas; Creighton, Claudia; Hameed, Nishar; Naebe, Minoo; Henderson, Luke C.; Setty, Mohan; Fox, Bronwyn L.
Abstract: Here we report on the role of oxygen in the evolution of radial heterogeneity in the fibre structure and properties of PAN fibres stabilized in air and vacuum at different temperatures. Modulus mapping by Nano-indentation showed heterogeneous modulus distribution in the fibres treated in air, while no variation in modulus was observed in fibres processed in vacuum. Raman spectroscopy and elemental analysis revealed that the temperature dependent oxygen diffusion from skin to core of the fibres assisted in the evolution of higher extent of sp 2 -hybridized carbons in the skin compared to core of the air treated samples. Conversely, no radial structure variations were observed in the vacuum treated fibres. Higher modulus in the skin of air-treated fibres was due to the formation of compact structures which was associated with the enhanced intermolecular interactions facilitated by the formation of C=C bonds within the polymer backbone, promoted by oxidative-dehydrogenation reaction. Supporting these observations, the fracture morphology examined by SEM showed a brittle fracture in the skin and ductile fracture in the core.